2015
DOI: 10.1136/archdischild-2014-308057
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive neurally adjusted ventilatory assist in preterm infants: a randomised phase II crossover trial

Abstract: Registered with http://www.clinicaltrials.gov (NCT01877720).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 27 publications
6
67
3
Order By: Relevance
“…The ventilator data were downloaded from the ventilator, as we described previously . Considering the time for adjusting to the new setting, data recorded for the last 5 minutes of each NAVA level was used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ventilator data were downloaded from the ventilator, as we described previously . Considering the time for adjusting to the new setting, data recorded for the last 5 minutes of each NAVA level was used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Neurally adjusted ventilatory assist (NAVA), a technique that uses the electrical activity of the diaphragm (Edi) to control respiratory support and the NAVA level as an amplification factor that converts the Edi signal into a proportional pressure, has been developed and evaluated in many studies. Compared with conventional modes, NAVA in preterm infants improves patient‐ventilator synchrony, decreases delivered pressure or V T , and effectively reduces the work of breathing . In addition, unlike pressure‐ or volume‐targeted modes, the delivered pressure during NAVA is continually adjusted based on the Edi signal .…”
Section: Introductionmentioning
confidence: 99%
“…Given that airway patency enables transmission of pressure to the distal airways during inspiration, synchronized delivery of ventilator cycles via Edi increases the efficacy of NIPPV . A small prospective cross‐over trial noted a reduction of asynchrony events and respiratory effort with NIV‐NAVA . In addition, one cross‐over study comparing NIV‐NAVA and NIPPV in preterm infants reported a reduction in peak inspiratory pressure (PIP), inspiratory O 2 fraction (FiO 2 ) and the frequency of desaturation with NIV‐NAVA .…”
mentioning
confidence: 99%
“…In the NAVA group in this study, the patients received less frequent courses and doses of dexamethasone than the patients in the other group. No published evidence indicates that NAVA could accelerate weaning off the ventilator in preterm infants with severe BPD, but previous studies have shown that respiratory work and delivered peak pressure were lowered with NAVA while preserving respiratory effort in preterm infants . These advantages of NAVA might help preterm infants to be weaned off more easily while preventing further lung injury, but more studies are needed to verify the effect of NAVA on the ventilator weaning process in preterm infants.…”
Section: Discussionmentioning
confidence: 99%